Toward integrated DoD biosurveillance : assessment and opportunities - Moore, Melinda; Fisher, Gail; Stevens, Clare (Research report (Rand Corporation), 2013)
Biosurveillance is a cornerstone of public health. In July 2012, the White House issued the National Strategy for Biosurveillance, which defines the term and sets out key functions and guiding principles. The Department of Defense (DoD) carries out biosurveillance to monitor the health of military and affiliated populations and supports biosurveillance in other countries through a range of programs across the department. The Deputy Secretary of Defense issued interim guidance in June 2013 for implementation of the new National Strategy. This begins to set formal policy for DoD's biosurveillance enterprise. The Office of Management and Budget (OMB) recognized the importance of effective DoD biosurveillance not only for the department itself but also within the context of the National Strategy. With this in mind, OMB tasked DoD to carry out a comprehensive examination of its biosurveillance enterprise to determine priority missions and desired outcomes, the extent to which DoD biosurveillance programs contribute to these missions, and whether the current funding system is appropriate and how it can be improved to ensure stable funding.